2020
DOI: 10.1038/s41598-020-73840-4
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 and nesfatin-1-like peptide suppress growth hormone synthesis via the AC/PKA/CREB pathway in mammalian somatotrophs

Abstract: Nesfatin-1 (NESF) and NESF-like peptide (NLP), encoded in nucleobindin 2 and 1 (NUCB2 and NUCB1), respectively, are orphan ligands and metabolic factors. We hypothesized that NESF and NLP suppress growth hormone (GH) synthesis, and aimed to determine whether mammalian somatotrophs are a source and site of action of these peptides. Using immortalized rat somatotrophs (GH3 cells), NUCB expression was determined by qPCR, immunofluorescence and Western blot. NESF and NLP binding to GH3 cells was tested using fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…An inverse association between GH and irisin levels has been observed in humans, as the administration of recombinant human GH in young patients with Turner syndrome increased the circulating levels of irisin ( 281 ). We have reported that two novel metabolic peptides, nesfatin–1 and nesfatin–1–like peptide, are negative modulators of the synthesis of pituitary GH in mammals ( 166 ). Although their receptors are still unknown, it is expected that these peptides act through GPCR ( 282 ).…”
Section: Other Gh Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse association between GH and irisin levels has been observed in humans, as the administration of recombinant human GH in young patients with Turner syndrome increased the circulating levels of irisin ( 281 ). We have reported that two novel metabolic peptides, nesfatin–1 and nesfatin–1–like peptide, are negative modulators of the synthesis of pituitary GH in mammals ( 166 ). Although their receptors are still unknown, it is expected that these peptides act through GPCR ( 282 ).…”
Section: Other Gh Inhibitorsmentioning
confidence: 99%
“…Although their receptors are still unknown, it is expected that these peptides act through GPCR ( 282 ). It has been shown that both nesfatin–1 and nesfatin–1–like peptide regulate GH in the rat somatotrophs through the AC/PKA/CREB signaling pathway ( 166 ), suggesting that the mechanism of action of nesfatin–1 and nesfatin–1–like peptide involves a GPCR associated with an inhibitory Gα–subunit (Gαi). As discussed in the previous section, numerous pharmacological inhibitors were also used for the study of GH and somatotrophs ( Figure 2 ) .…”
Section: Other Gh Inhibitorsmentioning
confidence: 99%
“…In a very recent study, both NESF and NLP have been shown to inhibit GH synthesis and its ghrelin-induced release in mammalian somatotrophs ( 120 ). This study was carried out in cultured cell lines (GH3 and RC-4B/C) in which the authors demonstrated that both nucb1 and nucb2 mRNA expression existed, as well as their corresponding NUCB1 and NUCB2 proteins.…”
Section: Nesfatinsmentioning
confidence: 99%
“…We recently reported the first evidence of a GH suppressive effect for nesfatin-1 on rat somatotrophs. 17 Based on this, the pituitary localisation of its mRNA and other evidence on nesfatin-1 effects in fish, we hypothesised that nesfatin-1 is produced in the pituitary somatotrophs and inhibits the GH/IGF axis in goldfish (C. auratus). Here we report the results from our studies testing these hypotheses.…”
mentioning
confidence: 96%
“…16 Another example of a newly identified GH regulator is nesfatin-1. 17 Nesfatin-1 is an 82 amino acid peptide cleaved from the Nterminal of its precursor nucleobindin-2 (NUCB2). This peptide was first discovered in the rat hypothalamus 18 but later identified in other vertebrate groups, including fish.…”
mentioning
confidence: 99%